Addressing illegal practices: intergenerational transfer and creative engagement as a way to compensate boomerang effects - Richter, Isabell; Lim, Voon Ching; Fadzil, Kamal Solhaimi Bin; Riordan, Oliver; Pahl, Sabine; Goh, Hong Ching (Frontiers in Communication, 2023)
This study examines the effectiveness of using an educational comic book in intergenerational transfer of knowledge and intentions regarding dynamite fishing in Borneo, Malaysia. The findings demonstrate that intergenerational transfer of knowledge occurred both in the short and long term from the children to the parents. The success of intergenerational transfer on intentions was twofold. The intention to talk about the problem within the community was transferred from children to their parents at the second measurement point indicating that the development of new intentions takes time. A boomerang effect was found for the intention to stop the practice of dynamite fishing within the individuals who rely on fishing for their livelihood. This rebound effect only occurred in the control group and was mitigated by engagement with the comic book in the treatment group. Overall, these results emphasize the significance of considering both, motivational as well as economic drivers of dynamite fishing. In addition, it is emphasized that careful monitoring of unintended reactions within participant groups, including control groups, is necessary, particularly in cases where research inquiries revolve around sensitive topics.